CULTURAL AND HISTORICAL ESSENCE OF IRONY IN MODERN PHILOSOPHY - Geiko, S. M. (Anthropological Measurements of Philosophical Research, 2012)
The author of article researches the cultural and historical essence of irony in the modern philosophy. The role of irrational searches of philosophical discourse of modernism in the process of «irony» term explication is argumented. The possibility of «irony» therapeutical function execution in post modernistic style of philosophical research is proved.